Management strategies to minimize the dredging impacts of coastal development on fish and fisheries - Wenger, A.; Rawson, Christopher; Wilson, S.; Newman, Stephen; Travers, M.; Atkinson, S.; Browne, Nicola; Clarke, D.; Depczynski, M.; Eftermeijer, P.; Evans, R.; Hobbs, J.; et al. (Wiley-Blackwell, 2018)
Accelerating coastal development and shipping activities dictate that dredging operations will intensify, increasing potential impacts to fishes. Coastal fishes have high economic, ecological, and conservation significance and there is a need for evidencebased, quantitative guidelines on how to mitigate the impacts of dredging activities. We assess the potential risk from dredging to coastal fish and fisheries on a global scale.We then develop quantitative guidelines for two management strategies: threshold reference values and seasonal restrictions. Globally, threatened species and nearshore fisheries occur within close proximity to ports. We find that maintaining suspended sediment concentrations below 44 mg/L (15–121 bootstrapped CI) and for less than 24 hours would protect 95% of fishes from dredging-induced mortality. Implementation of seasonal restrictions during peak periods of reproduction and recruitment could further protect species from dredging impacts. This study details the first evidence-based defensible approach to minimize impacts to coastal fishes from dredging activities.